Prevalence of cardiac amyloidosis among elderly patients with systolic heart failure or conduction disorders. (3rd July 2019) - López-Sainz, Ángela; de Haro-del Moral, F. Javier; Dominguez, Fernando; Restrepo-Cordoba, Alejandra; Amor-Salamanca, Almudena; Hernandez-Hernandez, Aitor; Ruiz-Guerrero, Luis; Krsnik, Isabel; Cobo-Marcos, Marta; Castro, Victor; Toquero-Ramos, Jorge; Lara-Pezzi, Enrique; et al.
Abstract: Objective: Cardiac amyloid infiltration can lead to systolic heart failure (HF) or to conduction disorders (CD). Patients with transthyretin (ATTR) amyloidosis are particularly exposed. We sought to determine the prevalence of ATTR and AL among patients >60 years admitted with CD or unexplained systolic HF and increased wall thickness. Materials and Methods: We studied 143 patients (57% males, 79 ± 9 years) with HF ( N  = 28) or CD requiring pacemaker implantation ( N  = 115). In total, 139 (97%) patients (28 with HF and 111 with CD) underwent 99m Tc-DPD scintigraphy to detect ATTR, and 105 (73%; 19 HF and 86 CD) underwent AL screening. Results: Five patients (4%; 95%CI:0–7%) exhibited wild-type ATTR (ATTRwt) amyloidosis, 2 (2%; 95%CI:0–4%) had CD and 3 (11%; 95%CI:0–23%) HF. No patient showed AL. The 2 ATTRwt patients with CD were previously asymptomatic, did not show classical ECG signs and exhibited mild LV hypertrophy with preserved LVEF. By contrast, all ATTRwt patients with HF had ECG and echocardiographic signs of amyloid. During a mean follow-up of 18 ± 11 months, 3(60%) patients with ATTRwt amyloidosis (1 CD and 2 HF) and 14(10.4%) without died. Conclusion: Prevalence of ATTRwt amyloidosis in patients with CD requiring pacemaker is low. Although, additional studies are needed, prevalence seems to be higher in elderly patients with systolic HF.